Traditional cuisine as a social symbol: A socio-cultural analysis of the collective identity of Indonesian society - Nadra, Nyoman Mastiani; Sumawidari, Ida Ayu Ketut; Damayanti, Ida Ayu Kade Werdika; Arjana, I Wayan Basi (Journal of Commerce, Management, and Tourism Studies, 2025)
This study aims to explore the role of traditional culinary arts as a symbol of cultural identity and an instrument of Indonesian cultural diplomacy internationally. The research focuses on how regional cuisine reflects local values and community history, and is strategically used in cultural diplomacy through festivals, diaspora restaurants, and national programs such as Spice Up the World. A descriptive qualitative approach is used to analyze representations of traditional culinary arts in mass media, cultural policies, and digitalization practices. Data were obtained from academic literature, case studies (in Australia and Toronto), digital content such as culinary TikTok, and interactive media campaigns. The findings indicate that traditional cuisine not only strengthens ethnic identity and collective memory but also plays a role in shaping international perceptions of Indonesia. Digital media increases visibility but also brings challenges in the form of commodification and the narrowing of cultural meaning. Diaspora restaurants have proven effective as agents of gastrodiplomacy, while government programs enhance national branding through food. The study concludes that traditional cuisine is a strategic medium that bridges local and global values. If utilized holistically and sustainably, culinary can strengthen Indonesia's cultural image while opening up a more inclusive and competitive diplomatic space.